Upaya Meningkatkan Minat Baca Siswa SD melalui Literasi Digital - Tasya, Anas; Lorenza, Dina Mauliya; Maria, Fanny Luche; Lita, Lita (TSAQOFAH, 2023)
Interest in reading can grow by itself in each individual, by getting used to reading activities, each individual will have broader knowledge. Reading is one of the means to learn about the world that you want to know, helps students to learn various knowledge, adds information and can also add to students' vocabulary that they did not know before. Thus reading is very important for students. This reading activity is an activity that can improve HR. In writing this article, the author uses the literature study method. which this method is to collect a number of books, library data, read and review the materials and sources of information that have been collected. The author collects data sourced from journals, scientific articles, and literature reviews that contain concepts written by researchers. Interest is an attitude that exists within a person or as special attention to certain things, this is formed because of the desire and feeling of happiness that arises from within a person. Interest in reading comes gradually, like a growth chart. Based on the results of the research and discussion, it can be concluded that the reading interest of elementary school children is currently still low. Efforts to increase students' interest in reading can be done by utilizing technology, namely the use of digital literacy. besides that increasing students' interest in reading can also be influenced by internal or external factors, then in an effort to increase students' interest in reading, teachers and parents also play an important role in fostering motivation and increasing interest in reading from within these students.